SHUI RUMAH TINGGAL : TINDAKAN SOSIAL DAN MAKNANYA BAGI ETNIS TIONGHOA DI KOTA PEKANBARU - Kenzia Ardaneshwary Rinson; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
For the Ethnic Chinese community, Feng Shui is considered a good, worthy and proper value so that its existence is considered important in life. Feng Shui residence is basic, because the house is the center of all life activities. Their actions are influenced by various motivations that give rise to social actions that underlie Chinese ethnicity doing Feng Shui. The formulation of the problem discussed in this study is how the background of ethnic Chinese social actions in the application of residential Feng Shui and why residential Feng Shui is still used by ethnic Chinese in Pekanbaru city. The subjects of this study were 4 people consisting of various levels of society. With descriptive qualitative research methods and using social action theory from Max Weber, this study can conclude that the actions of the Chinese Ethnic in Pekanbaru in carrying out Feng Shui are based on 4 kinds of social actions, namely (1) instrumental rational action, (2) value-oriented rational action, (3) traditional action and (4) affective action. The suitability of Feng Shui analysis with the logical truth that has been passed down from generation to generation, as well as the success of the Chinese community, shows that Feng Shui is the values that can bring good luck, which is the main key so that the practice of Feng Shui survives in today's modernity.Keywords: Feng Shui, Residential House, Social Action